Leading Through Distance: Transformational Leadership and Internal Crisis Communication in Hybrid Work Models - Asmianur, Reffa (Communica : Journal of Communication, 2025)
The COVID-19 pandemic accelerated the global adoption of hybrid work models and raised new challenges for internal crisis communication. This study examines how transformational leadership clarifies communication and strengthens employee engagement in multinational hybrid environments. A comparative qualitative case study of six firms was conducted through interviews, observations, and document analysis, with thematic analysis and triangulation applied. The findings show that transformational leadership improves clarity, trust, and engagement by fostering transparency, responsiveness, and empathy. Inclusive and adaptive strategies proved most effective in overcoming fragmented communication in hybrid models. The study also highlights that post-pandemic communication works best with flatter hierarchies, integrated digital tools, and feedback-rich systems, while transactional leadership often created gaps. This study contributes novelty by specifically examining transformational leadership in internal crisis communication within multinational hybrid environments, a topic rarely addressed in prior research. The research also underlines the relevance of Leader-Member Exchange and Situational Leadership theories in explaining effectiveness across industries. Limitations include qualitative subjectivity, small sample size, and fast-changing organizational contexts. Practically, the study suggests that organizations should equip leaders with empathetic and adaptive communication skills to sustain cohesion in hybrid settings.